ANALISIS MANAJEMEN RANTAI PASOK DI PERUM BULOG SUB DIVRE SUMBAWA PRODUK PERTANIAN JENIS BERAS - Muliana; Shafwan Amrullah (The Journal of Teknologi Pangan, 2022)
In Indonesia, the agricultural sector plays an important role in the national economy. One of the agricultural products that plays an important role is rice. Because Sumbawa Besar Regency is one of the suppliers of rice or rice to several areas, so that if there is a drastic decline in rice production and productivity in Sumbawa Regency, it will affect food availability for most areas that need it it is necessary to make a prediction to find out how the future picture will be whether rice production in Sumbawa Besar district has increased or decreased. Supply chain management is a comprehensive review and integrated, integrated and interrelated management from upstream (production input) to downstream. This study aims to determine supply chain management at Perum Bulog Sub-Divre Sumbawa to meet the needs of the Sumbawa community. In this study, researchers used qualitative research methods, so that researchers can explore more broadly and deeply about supply chain management. Supply chain management at Perum Bulog Sub Divre Sumbawa has not run optimally, this can be seen from rice procurement and rice sales which are still unstable from 2019-2021. . Sales of medium rice at Perum Bulog Sub Divre Sumbawa in 2019 reached 442,604 Kg, in 2020 sales reached 730, 615 Kg, and in 2021 it reached 170,520 Kg.